2012
DOI: 10.1007/s00159-012-0050-3
|View full text |Cite
|
Sign up to set email alerts
|

Multiple populations in globular clusters

Abstract: Recent progress in studies of globular clusters has shown that they are not simple stellar populations, being rather made of multiple generations. Evidence stems both from photometry and spectroscopy. A new paradigm is then arising for the formation of massive star clusters, which includes several episodes of star formation. While this provides an explanation for several features of globular clusters, including the second parameter problem, it also opens new perspectives about the relation between globular clu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
765
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 757 publications
(787 citation statements)
references
References 340 publications
20
765
0
2
Order By: Relevance
“…Several studies have revealed the existence of multiple stellar populations, having different chemical compositions, in globular clusters that have been subjected to a detailed abundance analysis (e.g., see Gratton, Carretta & Bragaglia 2012;Piotto et al 2015). M4 is no exception, and the presence and properties of two main populations is well documented in the literature (see e.g.…”
Section: Comparison With Independent Estimates Of Mass and Distancementioning
confidence: 99%
“…Several studies have revealed the existence of multiple stellar populations, having different chemical compositions, in globular clusters that have been subjected to a detailed abundance analysis (e.g., see Gratton, Carretta & Bragaglia 2012;Piotto et al 2015). M4 is no exception, and the presence and properties of two main populations is well documented in the literature (see e.g.…”
Section: Comparison With Independent Estimates Of Mass and Distancementioning
confidence: 99%
“…In spite of their multiple populations (see Gratton, Carretta & Bragaglia 2012), these systems offer well constrained tests for stellar evolution theory. Their colour magnitude diagrams (CMD, hence photometry) provide two clear evolutionary diagnostics for the stellar models -the main-sequence turn-off (MSTO) magnitude and the magnitude of the bump in the red giant branch (RGB) luminosity function (LF bump or bump hereinafter).…”
Section: Introductionmentioning
confidence: 99%
“…First, it has been known for several decades that globular clusters exhibit star-to-star variations in the CN and CH line strengths (e.g., Smith 1987). These molecular line strength variations are driven by star-to-star abundance variations for the light elements from C to Al (see reviews by Kraft 1994and Gratton et al 2004, 2012a for details.) Secondly, a star-to-star dispersion in iron-peak elements, and other elements, has long been known to exist in the globular cluster ω Centauri (e.g., Freeman & Rodgers 1975;Cohen 1981;Norris & Da Costa 1995;Smith et al 2000;Johnson & Pilachowski 2010).…”
Section: Introductionmentioning
confidence: 99%